Scale validation and associated factors with ethical climate in health services: methodological study (Brazilian Journal of Health Research, 2025)
Introduction: Organizational ethical climate is an important indicator of working conditions in healthcare, influencing professionals' well-being, quality of care, and organizational outcomes. However, no validation studies of the Hospital Ethics Climate Survey (HECS) were identified for the Brazilian context. Objective: To seek evidence of internal structure validity and reliability of an organizational ethical climate scale through its translation, adaptation, and application for nurses and physicians in primary and hospital care services. Methods: This methodological study involved the translation, adaptation, and validation of the HECS instrument. Participants included 5 researchers, 4 translators, and 20 experts in the translation and adaptation process, 41 healthcare professionals in the pre-test, and 134 professionals in the validation phase, conducted in southern Brazil between 2021 and 2022. Statistical analyses included exploratory and confirmatory factor analysis, Cronbach’s Alpha, McDonald’s Omega, Pearson’s chi-square test, and Student’s t-test. Results: Exploratory analysis showed KMO=0.892, Bartlett p
Keywords: Institutional ethics; Validation study; Health Care Professionals; Health services